Antibacterial resistance: A comparative study between clinical and environmental isolates based on whole cell protein profiling by SDS-PAGE - Adnan, Shoaib (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2015